URGENSI PENGEMBANGAN KOMPETENSI GURU DALAM MEWUJUDKAN PROFESIONALISME DI BIDANG PENDIDIKAN - Intan Munadifa; Moh. Burhanus Sholichin; Munawir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article discusses the urgency of improving teacher competence, especially Islamic Religious Education (PAI) teachers, in achieving professionalism amid the dynamics of the industrial revolution 4.0 and society 5.0. Digital transformation has shifted the paradigm of teacher professionalism from merely mastering subject matter to more integrative abilities, including digital literacy, pedagogical innovation, and the application of differentiated learning. This study uses a literature review method with a qualitative approach through the examination of various relevant literature sources. The results show that the integration of technology in the learning process, such as the use of interactive media, digital platforms, and artificial intelligence, plays a significant role in improving learning effectiveness and student engagement. In addition, the Professional Learning Community (PLC) approach has proven to be a sustainable strategy in improving teacher competence through collaboration, reflection, and sharing best practices. However, the implementation of teacher competence development still faces several challenges, such as gaps in digital literacy, school culture that is not yet fully collaborative, and leadership that is not yet optimal. Therefore, a systemic transformation is needed that integrates technology, strengthens professional culture, and provides data-based policy support to encourage teacher professionalism that is adaptive and relevant to the demands of the 21st century.